The Effectiveness of Using The Quizizz Website Learning Media To Improve Female Students' Learning Outcomes In Arabic Language Lessons In Class 7 At Mts Muallimat Cukir Jombang College - Alfi, Nurina; Rohman, Fathur Rohman (Universitas Al-Amien Prenduan, 2025)
This research study investigates the impact of using the interactive learning platform Quizizz on improving Arabic language learning outcomes in grade 7 female students. Using quantitative methods and a quasi-experimental design, this study compares learning outcomes between the group using Quizizz and the control group, This research aims to determine the effectiveness of using the quizizz website learning media to improve female students' learning outcomes in Arabic language lessons in class 7 at Mts Muallimat Cukir Jombang College. This research uses quantitative research methods. The method used is a quantitative method using a Quasi Experimental research type. The sampling technique used is a non-probability sampling technique with equivalence sampling which includes experimental separation and arbitration separation. The research results show that: the researcher carried out treatment in the experimental class using Quizizz Lesson learning and then they were given a test via the Quizizz application. After students are presented with questions using Quizizz, then continue with the test after providing an explanation of the material. The results of applying the Quizizz learning method have progressed, it is known that the average experimental semester result is 94.14, which is higher than the average arbitration semester result of 61.07. There is effectiveness in using educational tools on the